Alcohol consumption in rheumatoid arthritis: A path through the immune system - Azizov, Vugar; Zaiss, Mario (Nutrients, 2021)
Benefits and harms of different components of human diet have been known for hundreds of years. Alcohol is one the highest consumed, abused, and addictive substances worldwide. Con-sequences of alcohol abuse are increased risks for diseases of the cardiovascular system, liver, and nervous system, as well as reduced immune system function. Paradoxically, alcohol has also been a consistent protective factor against the development of autoimmune diseases such as type 1 diabetes, multiple sclerosis, systemic lupus erythematosus, and rheumatoid arthritis (RA). Here, we focused on summarizing current findings on the effects of alcohol, as well as of its’ metabolites, acetaldehyde and acetate, on the immune system and RA. Heavy or moderate alcohol consumption can affect intestinal barrier integrity, as well as the microbiome, possibly contributing to RA. Additionally, systemic increase in acetate negatively affects humoral immune response, diminishing TFH cell as well as professional antigen-presenting cell (APC) function. Hence, alcohol consumption has pro-found effects on the efficacy of vaccinations, but also elicits protection against autoimmune diseases. The mechanism of alcohol’s negative effects on the immune system is multivariate. Future studies addressing alcohol and its’ metabolite acetate’s effect on individual components of the immune system remains crucial for our understanding and development of novel therapeutic pathways.
CRIS-Team Scopus Importer:2021-05-14
Keywords: Acetaldehyde; Acetate; Alcohol; RA; Rheumatoid arthritis